2010
DOI: 10.1158/1940-6207.capr-09-0185
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Suppresses Lung Cancer Cell Growth through Ras–GTPase-Activating Protein SH3 Domain-Binding Protein 1

Abstract: Green tea is a highly popular beverage globally. Green tea contains a number of polyphenol compounds referred to as catechins, and (−)-epigallocatechin gallate (EGCG) is believed to be the major biologically active compound found in green tea. EGCG has been reported to suppress lung cancer, but the molecular mechanisms of the inhibitory effects of EGCG are not clear. We found that EGCG interacted with the Ras-GTPase-activating protein SH3 domain-binding protein 1 (G3BP1) with high binding affinity (K d = 0.4 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 27 publications
(34 reference statements)
2
68
0
Order By: Relevance
“…Our findings that RBP42 binds F1-ATPase mRNAs and many more mRNAs involved in energy metabolism in trypanosomes may help facilitate the discovery of additional G3BP targets in metazoans. Indeed, G3BP is altered in several cancer cells, and its binding to F1-ATPase and c-Myc mRNAs has been speculated to play a role in the metabolic changes that occur during altered cell growth (Guitard et al 2001;Tourriere et al 2001;Ortega et al 2010;Shim et al 2010;Cairns et al 2011). It will be interesting to see whether RBP42 also plays a role in adjusting the bioenergetics in trypanosomes, possibly in response to the constantly changing nutritional environment during the parasite life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that RBP42 binds F1-ATPase mRNAs and many more mRNAs involved in energy metabolism in trypanosomes may help facilitate the discovery of additional G3BP targets in metazoans. Indeed, G3BP is altered in several cancer cells, and its binding to F1-ATPase and c-Myc mRNAs has been speculated to play a role in the metabolic changes that occur during altered cell growth (Guitard et al 2001;Tourriere et al 2001;Ortega et al 2010;Shim et al 2010;Cairns et al 2011). It will be interesting to see whether RBP42 also plays a role in adjusting the bioenergetics in trypanosomes, possibly in response to the constantly changing nutritional environment during the parasite life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report has indicated that G3BP1 is a direct target of EGCG in lung cancer repression [15] . To determine whether the anti-fibrogenic effect of EGCG in LX-2 cells is mediated through G3BP1, we manipulated G3BP1 expression in these cells.…”
Section: Egcg Significantly Repressed Liver Fibrogenic Gene Expressiomentioning
confidence: 98%
“…Detailed molecular mechanistic studies have indicated that EGCG can regulate multiple signal transduction pathways in vitro in HSCs [10][11][12][13][14] , including those involving PDGF-BB, Rho, glutathione synthesis, collagen production and collagenase activity. In particular, Shim et al [15] have identified Ras-GTPase-activating protein SH3 domain-binding protein 1 (G3BP1) as a direct target of EGCG in lung cancer cells, in which EGCG suppresses cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…Certain phytochemicals are particularly eligible for the single compound type modality inasmuch as they are pleiotropic modulators of manifold signal transduction pathways and exhibit relatively low toxicity in non-cancerous cells (Khan et al, 2008;Lee et al, 2011b). Unfortunately, the currently Food and Drug Administration (FDA)-approved chemotherapeutic phytochemicals such as paclitaxel, docetaxel, vinblastine, and vincristine have only a singular molecular target (tubulin), whereas other phytochemical candidates such as (-)-epigallocatechin gallate and delphinidin have multiple molecular targets (Ermakova et al, 2006;Li et al, 2007;He et al, 2008;Kang et al, 2008;Shim et al, 2008Shim et al, , 2010Hwang et al, 2009;Ozbay and Nahta, 2011) and in vitro cytostatic/cytotoxic potency (Bin Hafeez et al, 2008;Hsieh and Wu, 2009;Philips et al, 2009;Qiao et al, 2009;Yun et al, 2009;Cvorovic et al, 2010;Das et al, 2010) but lack an advanced clinical development trajectory and regulatory approval status.…”
Section: Introductionmentioning
confidence: 99%